Diversity and Conservation Status of Gelodok Fish (Perciformes: Gobiidae) in East Pohuwato Coastal Area, Gorontalo Province, Indonesia - Cono, Titi Hawanda Metania; Hasim, Hasim; Hamidun, Marini Susanti; Baderan, Dewi Wahyuni. K; Dunggio, Iswan (Bioeksperimen: Jurnal Penelitian Biologi, 2024)
This study aims to determine the diversity and conservation status of Gelodok fish in the Pohuwato Coastal Mangrove Area. Data collection techniques were carried out by surveying the location to see the conditions and determine the sampling site. Sampling was done by cruising method using 3x3 meter size net. The fish found then analyzed the level of diversity and conservation status. The results showed that the spadefish found in the mangrove area of East Pohuwato Village consisted of two species of spadefish, namely Periophthalmus malaccensis and Periophthalmus argentilineatus with a diversity value of 0.17016 classified as low diversity. The conservation status of Periophthalmus malaccensis is included in the Data Deficient (DD) category and Periophthalmus argentilineatus is included in the Least Concern (LC) category based on the IUCN Red List of Threatened Species (IUCN)